Evaluation of the Effectiveness of Open Source Software in Image-Based 3D Modeling - أسد غيث; عمر الخليل; أحمد علي (Latakia University Journal -Engineering Sciences Series, 2023)
3D modeling software that come with a 3D laser scanner is usually expensive and requires a high level of expertise. On the other hand, image-based modeling software offers a cheaper alternative that can be handled with relative ease. Free and open source software is also available that has the ability to produce high quality data for 3D modeling. However, contemporary academic research rarely provides survey-based feature lists or a critical examination of the potential workflows of these programs, nor does it usually provide guidance for non-experts interested in learning, developing, and sharing 3D content on a budget. To address these problems, a group of open source software is studied in this paper based on its features, workflow, 3D processing time and accuracy.In this paper, a set of real data was used to compare and evaluate two open source software (VisualSfM and Mishroom) based on the point clouds they produce. To do this, these clouds were compared with a reference cloud generated using commercial 3DF Zephyr Aerial software using CloudCompare software. The results showed that the use of these software in 3D modeling gives promising results, accurate with its ease of use. We believe that this research will help non-expert users understand the topic of photogrammetry and determine the most suitable software for producing low-cost and high-quality 3D image-based models